Universal structure of subleading infrared poles at strong coupling - Alday, L (2009)
Recently a concise expression for the subleading infrared singularity of dimensional-regularized gauge theories has been proposed. For conformal theories, such relation involves a universal eikonal contribution plus a non-eikonal contribution, related to the subleading term in the anomalous dimension of twist two operators with large spin. In this note we make use of the AdS/CFT correspondence in order to check such conjecture at strong coupling for the case of = 4 SYM. © SISSA 2009.